Kinetic and structural studies on the interactions of Torpedo californica acetylcholinesterase with two donepezil-like rigid analogues - Rosanna Caliandro; Alessandro Pesaresi; Luca Cariati; Antonio Procopio; Manuela Oliverio; Doriano Lamba (Taylor & Francis Group, 2018)
Acetylcholinesterase inhibitors were introduced for the symptomatic treatment of Alzheimer's disease (AD). Among the currently approved inhibitors, donepezil (DNP) is one of the most preferred choices in AD therapy. The X-ray crystal structures of Torpedo californica AChE in complex with two novel rigid DNP-like analogs, compounds 1 and 2, have been determined. Kinetic studies indicated that compounds 1 and 2 show a mixed-type inhibition against TcAChE, with Ki values of 11.12 ± 2.88 and 29.86 ± 1.12 nM, respectively. The DNP rigidification results in a likely entropy-enthalpy compensation with solvation effects contributing primarily to AChE binding affinity. Molecular docking evidenced the molecular basis for the binding of compounds 1 and 2 to the active site of β-secretase-1. Overall, these simplified DNP derivatives may represent new structural templates for the design of lead compounds for a more effective therapeutic strategy against AD by foreseeing a dual AChE and BACE-1 inhibitory activity.